PERAN HUMAS DALAM MENGEMBANGKAN PENDIDIKAN MELALUI OTONOMI PENDIDIKAN TINGGI - Siti Nur Jannah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Quality management at the moment is a phenomenon that requires special attention for a college, especially private colleges. This means that private universities, especially private universities in the city of Bandung to always be directed at improving quality activities. Because otherwise the private university lacks a place in the hearts of society that ultimately threatens its existence. A publicist is the bridge or the first path of an image that is formed in the community at a particular institution. The importance of applying this public relations strategy in marketing universities in every institution that requires the performance of a publicist to help the course of a work program, as well as public relations can maintain the image of an institution in the institution, so that an institution can be recognized and trusted by public relations strategy. Thus the focus of this study is the quality management of universities related to the study of the influence of visionary leadership and lecturer performance on the quality of the university.